Escavações em solos argilosos sobreconsolidados suportados por paredes mono-escoradas: Análise dos efeitos da anisotropia de permeabilidade - Juliana Cunha Esteves (2010)
When excavations in clayey soils are undertaken, the low permeability of these soils does not allow the instantaneous change of their water content, which implies the generation of excess pore pressures in the ground. With the time, the variations of the stress and strain states are associated to the dissipation of those excess pore pressures (consolidation), which influences long term behaviour of the work. Using a computer program based on the finite element method, a parametric study is conducted in order to evaluate the effects of permeability anisotropy on excavations in clayey soils supported by single propped walls. Particular attention is given, both during and after the constructive period, to the analysis of the excess pore pressures, stress levels and displacements in the ground, as well as the displacements, bending moments and pressures on the wall.